PENDAMPINGAN PENGOLAHAN SERBUK KAYU MENJADI DUPA DI DESA SUKAWATI - Komang Adi Tresna Putra; I Kadek Agus Windu Adi; Ida Bagus Teja Pramana; Luh Putu Mahyuni; Made Mulyadi (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
The problem faced by partner villages is that the added value of incense products is still low because they only focus on raw incense, do not yet have their market, because incense production is still based on orders, and the availability of biting raw materials is often lacking. The purpose of the community service program is to develop the business potential of incense in partner villages, namely Sukawati Village, Sukawati District, Gianyar Regency so that it can become the village's flagship product. The approach used in implementing this service program is Community Based Participatory Research (CBPR), which is a collaborative approach aiming to overcome community problems. The methods used are mentoring and providing education on making fragrant incense and packaging carried out by partners of successful entrepreneurs, assistance and consultation on trademark registration, and substitution of science and technology in the form of wood-biting smoothing machines into sawdust. The result of the activity is an increase in added value because it has produced and sold fragrant incense with the Gunung Katu brand marketed by business partners to the island of Bali, there is an increase in bamboo biting production because it has used the help of wood smoothing machines. The results of this service activity have an impact on increasing the income of the community in partner villages.  ---  Permasalahan yang dihadapi desa mitra adalah nilai tambah produk dupa masih rendah karena hanya fokus pada dupa mentah, belum memiliki pasar sendiri, karena produksi dupa masih berdasarkan pesanan, dan ketersediaan bahan baku biting sering kekurangan. Tujuan program pengabdian kepada masyarakat untuk mengembangkan potensi usaha dupa di desa mitra yaitu Desa Sukawati Kecamatan Sukawati Kabupaten Gianyar, agar bisa menjadi produk unggulan desa. Pendekatan yang digunakan dalam pelaksanaan program pengabdian ini adalah Community Based Participatory Research (CBPR), yaitu pendekatan kolaboratif dengan maksud mengatasi permasalahan di masyarakat. Metode yang digunakan berupa pendampingan dan memberikan edukasi mengenai pembuatan dupa wangi dan pengemasan yang dilakukan oleh mitra dari pengusaha yang sudah berhasil, pendampingan dan konsultasi pendaftaran merek, dan substitusi ipteks berupa penggunaan mesin penghalus biting kayu menjadi serbuk kayu. Hasil kegiatan adanya peningkatan nilai tambah karena telah menghasilkan dan menjual dupa wangi dengan merek Gunung Katu yang dipasarkan oleh mitra pengusaha ke pulau Bali, ada peningkatan produksi biting bambu karena telah menggunakan bantuan mesin penghalus kayu. Hasil dari kegiatan pengabdian ini memberikan dampak pada peningkatan pendapatan masyarakat di desa mitra.